The identification of the development stages of the karstic fracture–cavity carbonate reservoirs: a case study on the lungu oilfield, Tarim basin - Chang, Shaoying; Wang, Mengxiu (Frontiers in Earth Science, 2023)
The challenge of identifying connectivity within karstic fracture-cavity reservoirs significantly impedes the efficient development of oil and gas resources, primarily due to our limited understanding of the developmental stages and distribution of these unique reservoirs. In this study, we employ a layered interpretation method to predict the distribution of various developmental stages within karstic reservoirs. In our approach, we first leverage our knowledge that karstic formations are primarily shaped by the water table. We reconstruct paleomorphological data and select representative wells in a chronological order from old to new. This process enables us to determine the karst base level and divide the karstic layers in individual wells. Subsequently, we identify small-scale karstic reservoirs and proceed to select isochronous sedimentary interfaces. We then flatten seismic events and map the karstic layers from wells to their corresponding seismic sections, a technique known as well-to-seismic calibration. Lastly, we provide accurate interpretations of the karstic layers, extracting root-mean-square amplitudes to predict the distribution of each reservoir. To validate the accuracy and efficiency of our method, we applied it to fracture-cavity reservoirs in the Lungu oilfield (LGX) of the Tarim Basin. Our results demonstrate the successful identification of 22 fracture-cavity reservoirs through an analysis of the distribution and connectivity of karstic reservoirs. This outcome serves as evidence that our method can significantly enhance reservoir production in terms of both efficiency and accuracy.